Smart Classroom-Based Learning: Difficulties and Challenges at Islamic Private Higher Education - Hidayat, Yusuf; Herniawati, Ani; Mahmud, Mahmud; Erihadiana, Mohamad (CV. Tripe Konsultan, 2024)
Smart classroom-based learning is a digital learning concept that combines the integrated digital technology and information system to improve the quality of learning process and interaction between lecturers and students. The study aims to identify benefits, difficulties, and solutions towards the implementation of smart classroom-based learning for the students at Islamic private higher education in Ciamis, West Java, Indonesia during participating the lecturing process. The study employs qualitative method under a case study. The findings of this study show that the implementation of smart classroom-based learning at Islamic private higher education in Ciamis, West Java is very useful for the students during participating the lecturing process. The evidences are shown by the percentage of 67.71%. In addition, (2) the most difficulties faced by the students during participating the lecturing process through the implementation of smart classroom-based learning is they cannot operate laptop and available digital tools. The evidences are shown by the percentage of 37.5%. Finally, the most solutions chosen by the students are asking for help to the IT staffs. These evidences are shown by the percentage of 41.67%. In conclusion, the implementation of smart classroom-based learning is very useful to support the quality of lecturing process at Islamic private higher education in Ciamis, West Java, Indonesia.